DOMINASI OTAK KANAN DAN OTAK KIRI TERHADAP HASIL BELAJAR MATEMATIKA - Vresty Yuning Diyas Prasetya (Universitas PGRI Adi Buana Surabaya, 2015)
Formulation of the problem in this study is Are there differences in mathematics learning outcomes material comparisons and scale among the students who use the process of thinking dominant right brain and students who use the process of thinking dominant left brain class of VII-J SMP Negeri 24 Surabaya. The purpose is to determine whether there is difference in mathematics learning outcomes material comparisons and scale among the students who use the process of thinking dominant right brain and students who use the process of thinking dominant left brain class of VII-J SMP Negeri 24 Surabaya. Data collection techniques in this study is using questionnaires and test methods. Methods of data analysis using t-test formula. From the analysis of the data obtained thit = -5,55 which located in the rejection H0. This means H0 denied and H1 reads Ã¢â‚¬Å“There are differences in mathematics learning outcomes material comparisons and scale among the students who use the process of thinking dominant right brain and students who use the process of thinking dominant left brain class of VII-J SMP Negeri 24 SurabayaÃ¢â‚¬Â be accepted. Then from the analysis of data and hypothesis testing can be concluded there are differences in mathematics learning outcomes material comparisons and scale among the students who use the process of thinking dominant right brain and students who use the process of thinking dominant left brain class of VII-J SMP Negeri 24 Surabaya school years 2014-2015. Keywords: dominant right brain, dominant left brain, mathematics learning outcomes method